ENTREPRENEURIAL MANAGEMENT AND UTILIZATION OF DIGITAL MARKETING FOR UMKM ACTORS IN NGARGOGONDO, BOROBUDUR DISTRICT, MAGELANG REGENCY - Hanung Eka Atmaja; Budi Hartono; Khairul Ikhwan (RADJA PUBLIKA, 2024)
The Ngargogondo tourist village is one of the tourist villages in the Borobudur Village Economic Hall area (Balkondes Borobudur). The community service program carried out in Ngargogondo Village, Borobudur District, Magelang Regency aims to find out the obstacles or problems experienced by MSME actors so that the problems can be identified which will then be used as guidance material for each MSME so that MSMEs can develop forward and encourage the community's economy. around. The methods used are counseling, tutorials and discussions. This article was analyzed descriptively qualitatively with the results of the service carried out, namely that Ngargogondo MSME participants who took part in the training were able to apply the entrepreneurial management knowledge and skills they acquired to manage and run their businesses, Ngargogondo MSME participants who took part in the training were able to formulate and implement business strategies, Ngargogondo MSME participants who took part in the training were able to innovate products in their respective MSMEs, Ngargogondo MSME participants who took part in the training were able to carry out digital marketing to expand market reach and Ngargogondo MSME participants who take part in the training know alternative markets for the products they produce.